Bioremediation of Pesticide-Contaminated Soils through Composting: Mechanisms, Factors, and Prospects - Wong, Wei Lin; Pangging, Monmi; Rubiyatno (Industrial and Domestic Waste Management, 2023)
Pesticide contamination of soils poses a significant environmental and agricultural challenge on a global scale, with escalating pesticide consumption in various regions. Composting has emerged as a cost-effective and sustainable bioremediation method for pesticide-contaminated soils. This review article delves into the mechanisms, factors influencing efficiency, and the pros and cons of composting as a strategy to address pesticide pollution in soils. Pesticides enter soil environments through both point sources, such as spillage from storage or disposal areas, and non-point sources, including intensive agricultural use and household applications. The physical and chemical characteristics of pesticides, coupled with soil factors like permeability and particle size, influence their fate and behavior in soils. Composting, as a bioremediation method, offers several advantages, including complete destruction of pesticide compounds through microbial degradation, transforming them into less hazardous products. Key factors affecting composting efficiency include nutrient availability, particle size, temperature, pH, oxygen, and moisture content, all crucial for microorganism growth and pesticide degradation. This article underscores the importance of maintaining optimal conditions for these factors to ensure the high performance and efficiency of pesticide degradation during composting. It also discusses the potential drawbacks of this method. Composting proves to be a promising and eco-friendly approach for remediating pesticide-contaminated soils, addressing both environmental concerns and the need for sustainable agricultural practices.